ChemInform Abstract: Regiocontrolled Synthesis of 3‐ and 5‐Aminopyrazoles, Pyrazolo[3, 4‐d]pyrimidines, Pyrazolo[3, 4‐b]pyridines and Pyrazolo[3, 4‐b]quinolinones as MAPK Inhibitors. Issue 4 (28th January 2014) - Bagley, Mark C.; Baashen, Mohammed; Paddock, Victoria L.; Kipling, David; Davis, Terence
Abstract This presents methods for the regioselective synthesis of 3‐ and 5‐aminopyrazoles and their transformation to polycyclic MAPK inhibitors, e.